Revisiting Queer Shame in Boys Love/Y Novels and Queer Literary Culture in Thailand - Prasannam, Natthanai (Journal of Arts and Thai Studies, 2025)
Background and Objectives: Following the legalization of same-sex marriage effective in 2025, Boys Love (BL)/Yaoi (Y), a globally recognized queer media, underscores its sociopolitical roles. The celebration of queer visibility and queer pride has gradually become the core value of the genre, influenced by LGBTQ political movements in the Euro-American context. The progressive-oriented approach is, however, challenged by the ideas of “Feeling Backward” proposed by Heather Love (2007). This study explores queer shame within the setting of Thai BL before and after its Queer Turn in 2020. The research aims to analyze queer shame in a selected case study, theneoclassic’s Phi Ai Num Mak or Ai, You Are So Fluffy (first published in 2021), before expanding to the queer literary culture in Thailand, which is potentially held in the cycle of shame. Methods: This study is categorized as qualitative research. The data selection relies on the exemplary case study method. The selected novel is explored by the textual analysis method and is situated within the shared context of related works. The case study is also employed as a tool for understanding broader phenomena: the queer literary culture in Thailand. Results: The development of Thai BL works is typically articulated in a progressive framework or transitioning from repression to the celebration of social movements. The analysis of queer shame in Ai, You Are So Fluffy illustrates how the novel challenges the conventions (ōdō) of BL originating from Japanese BL. The text redefines the rigid seme/uke formula and resonates with an emerging trend of queered character design in BL works of post-2020. The novel connotes that despite the sociopolitical movements of queers in Thailand, there are still different types of queer shame perpetuated within the queer communities. Nevertheless, queer shame is placed as a barrier to overcome through the framework of popular romance. Situating Ai, You Are So Fluffy as a bridge, queer shame in queer literary culture is realized in two directions: 1) the linkage between the development of Thai BL and the Thai literary tradition that presents queer-themed narratives, authored by both female and non-female writers since the late 1970s, and 2) the recovery of the marginalized history of female fans or consumers of BL media, along with the activities they engaged in since the period when BL content faced public condemnation, prior to the state’s incorporation of BL into soft-power policy in the early 2020s. Application of this study: The findings of the research have led to further explorations of Thai BL/Y across both the literary and media industries. In addition, it addresses the societal role of Thai BL through newly proposed critical views, as the concept of queer shame has not yet received significant attention in Thai scholarship. Conclusions: The study of queer shame in Thai BL novels provides an alternative perspective on the genre’s tradition, coinciding with the proliferation of digital media, transnational fan culture, and social activism. Rather than commemorating queer pride, queer shame can be leveraged as a significant aspect of certain queer communities. Some key notions from the research findings include 1) non-female BL writers recognize queer shame and generate political meaning from that very shame; 2) revisiting the BL genre alongside queer literary culture in Thailand revives queer spirits of the genre; and 3) queer shame unfolds the interplay among literary convention, screen adaptation, star persona, and fan culture within the Thai BL industry.